The transformation of higher education : convergence of distance and presence learning paradigms - Trindade, Armando Rocha (2008)
Conferência de abertura na Workshop IVETTE - Implementation of Virtual Environment in Training and Education, realizada na Universidade de Barcelona, de 16 a 18 de Novembro de 2000.